2014
DOI: 10.1590/0074-0276130224
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and seasonal abundance of sandflies (Diptera: Psychodidae: Phlebotominae) in coffee agroecosystems

Abstract: The composition and seasonal occurrence of sandflies were investigated in coffee agroecosystems in the Soconusco region of Chiapas, Mexico. Insect sampling was performed on three plantations located at different altitudes: Finca Guadalupe Zajú [1,000 m above sea level (a.s.l.)], Finca Argovia (613 m a.s.l.) and Teotihuacán del Valle (429 m a.s.l.). Sandflies were sampled monthly from August 2007-July 2008 using three sampling methods: Shannon traps, CDC miniature light traps and Disney traps. Sampling was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
5
16
3
4
Order By: Relevance
“…Picado et al (2010) studied the seasonal pattern of sand fly population in Nepal and they have observed that sand flies were positively associated with temperature and negatively associated with rainfall. In a coffee agroecosystem in Mexico, sand flies of the genus Lutzomyia showed positive correlation with temperature and negative correlation with rainfall (Jeanneth Pérez et al, 2014). However, in the present study P. argentipes, the wet zone hygroscopic species, which absorb moisture from atmospheric air were abundant during monsoon season in these settlements.…”
Section: Discussioncontrasting
confidence: 58%
“…Picado et al (2010) studied the seasonal pattern of sand fly population in Nepal and they have observed that sand flies were positively associated with temperature and negatively associated with rainfall. In a coffee agroecosystem in Mexico, sand flies of the genus Lutzomyia showed positive correlation with temperature and negative correlation with rainfall (Jeanneth Pérez et al, 2014). However, in the present study P. argentipes, the wet zone hygroscopic species, which absorb moisture from atmospheric air were abundant during monsoon season in these settlements.…”
Section: Discussioncontrasting
confidence: 58%
“…Shannon traps were by far the most efficient sampling method in this tropical forest. Similar results were obtained in several studies in the Mexican southeastern states of Campeche (Rebollar‐Téllez et al ., ; Pech‐May et al ., , ), Yucatan (Rebollar‐Téllez et al ., ), Quintana Roo (Cruz‐Ruiz et al ., ; Sánchez‐García et al ., ; May‐Uc et al ., ) and Chiapas (Pérez et al ., ). It is important to highlight that Shannon traps were primarily developed to collect sylvan mosquitoes using a horse as a bait during an epidemic of jungle yellow fever in Mato Grosso and Rio de Janeiro, Brazil (Shannon, ), and many years later, Pérez et al .…”
Section: Discussionmentioning
confidence: 97%
“…Os espécimes capturados foram sacrificados em vapores de éter (9) . Em seguida, os insetos foram armazenados em frascos plásticos contendo álcool 70% e identificados com data e local de captura (10) .…”
Section: Methodsunclassified